How do we ensure the qualification of civil servants with digital skills in Europe? A comparative study - NICA Elvira; MIȘA Anamaria; MELENCIUC Mihaela (Applied Research in Administrative Sciences)
Digital transformation has become a desire for states due to its real benefits to society. Public sector employees must prepare professionally to successfully implement digitisation projects of public services. In this context, the issue of digital skills of civil servants is a priority for the public administration. In this study, we performed a comparative analysis of institutions that provide professional training in the digital field for public sector employees. The purpose of this work is to analyse which are the models of good practices to follow when we talk about the digital transformation of public administrations in Europe. At the same time, the objective of the comparative analysis is to establish a set of priorities regarding the digital skills that must be pursued through the professional training processes of civil servants. The work offers interesting insights on how these institutions are sharing their responsibilities. The conclusions of this study can be useful to public institutions in Romania in order to improve digital transformation processes.